Battle of the sexes: An examination of male and female cyberbullying - Marcum, Cathy (2012)
Cyber bullying is defined as intentional, aggressive behavior toward another person that is performed through electronic means (i.e., computers, cell phones, PDAs) (Hinduja & Patchin 2007, 2008; Reekman & Cannard, 2009). In other words, it is behavior performed on the Internet that is intended to psychologically and emotionally harm someone. The present study will explore the differences in male and female cyber bullying in an undergraduate study, specifically in regard to posting gossip online with the intent to hurt others. The results indicate there are similar predictors of cyber bullying for the sexes, as well as unique predictors for male and female undergraduates